A Comporative Study on 8. Class Native Language Textbooks: The Case of Turkey and USA - İsmail Güleç; Tuğba Demirtaş (Sakarya University Journal of Education)
The purpose of this study is to determine the differences and the similarities between the textbooks used in the 8th year of the primary schools in Turkey for Turkish language education and those used in the 8th year of the primary schools in U.S.A. for English education at Massachusetts, Melrose Veterans Junior High. Since this study is aimed at determining the status, it has the nature of a descriptive study. The data in this study are grouped under three groups namely visual design (page design, text design and the designs of the visual elements), fields of learning (reading-writing-speaking-listening) , arrangement of the contents (type, theme) and these themes were compared with each other. The findings obtained within the thematic frame were declared and among these findings, several comparisons were made. Within the results obtained by interpreting these findings, it was determined that the American text books are richer in visual contents compared to the Turkish text books. Although the fields of learning are based on the basic skills in both countries (reading, writing, speaking, listening), several structural differences may be seen. Moreover, it was determined in the American text book that listening skills are not taken into consideration as different and separate fields of learning. The two books differ from each other in terms of their contents as well. The American text books are more diverse than Turkish text books and they are much richer than Turkish text books in terms of the themes, text types and the texts which represent them. In this context, by evaluating the language activities used in different countries, the activities, the methods and the technique used in Turkish text books should be developed and several environments for studying should be offered to the student.